Applying the pre-intentional phase of the Health Action Process Approach (HAPA) Model to investigate factors associated with intention on consistent condom use with various types of female sex partners among males who inject drugs in China. Issue 9 (1st September 2016) - Tsui, Hi Yi; Lau, Joseph T. F.; Wang, Zixin; Gross, Danielle L.; Wu, Anise M. S.; Cao, Wangnan; Gu, Jing; Li, Suning
ABSTRACT: Both drug injection and sexual transmission are the primary drivers of the HIV epidemic in China. This study investigated the prevalence and associated factors of intention of consistent condom use during sexual intercourse with female regular partners (RP), non-regular partners (NRP) and sex workers (FSW) among male people who inject drugs (PWID)in China. A total of 529 male non-institutionalized PWID aged 18–45 years with negative/unknown HIV status were recruited by multiple methods in Dazhou and Hengyang, China. The constructs of the pre-intention phase of the Health Action Process Approach (HAPA) Model, including partner-specific HIV risk perception, condom use positive outcome expectancies, condom use negative outcome expectancies, and self-efficacy of condom use, were assessed. The prevalence of behavioral intention of consistent condom use with RP, NRP, and FSW was 32.1%, 49.1%, and 63.6%, respectively. In multivariate stepwise analysis, conditional risk perception of HIV transmission via unprotected sex with RP/NRP/FSW was associated with intention of consistent condom use with these types of female sex partners (multivariate odds ratio (ORm) = 3.25–7.06). Condom use negative outcome expectancies were associated with intention of consistent condom use with RP and NRP (ORm = 0.30–0.46), while condom use self-efficacy was associated with intention of consistent condom use with RP and FSW in the next six months (ORm = 2.24–3.81). Male PWID are at high risk of HIV transmission through sexual behaviors. The pre-intention phase of the HAPA model may be applied to plan interventions to increase behavioral intention of consistent condom use with various types of female partners. Such interventions are warranted.